Solvent-induced redox isomerism of cobalt complexes with redox-active bisguanidine ligands - Lohmeyer, Lukas; Kaifer, Elisabeth; Himmel, Hans-Jörg (Inorganic chemistry, 2022)
Redox-isomeric coordination compounds, in which the magnetic and optical properties could be varied by a stimulated intramolecular electron transfer between the metal and a redox-active ligand, are of interest for several applications in catalysis and materials science. In this work, the redox chemistry of cobalt complexes with redox-active bisguanidine ligands is studied; systematic modifications at the redox-active bisguanidine and the co-ligand units allow for fine-tuning of the electronic structure, which eventually leads to the first observation of redox isomerism for cobalt complexes with redox-active guanidine ligands. Redox isomerism is triggered by a change in the solvent properties.